Unpacking the 'black box' of scanning probe microscopes for the next generation. (Research'eu results magazine)
Scanning probe microscope (SPM) techniques have evolved beyond imaging and manipulation with single atom resolution, to the sub-molecular and sub-atomic level. Yet, this success can jeopardise real process understanding, and so the EU-funded ACRITAS project set out to redress the balance.